2020
DOI: 10.2337/dc19-1586
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Influence of Social Determinants of Health on Glycemic Control in Elderly Adults With Diabetes

Abstract: This study aimed to understand the longitudinal relationship between financial, psychosocial, and neighborhood social determinants and glycemic control (HbA 1c ) in older adults with diabetes. RESEARCH DESIGN AND METHODSData from 2,662 individuals with self-reported diabetes who participated in the Health and Retirement Study (HRS) were used. Participants were followed from 2006 through 2014. Financial hardship, psychosocial, and neighborhood-level social determinant factors were based on validated surveys fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Overall, we observed that sex, ethnicity, education, and age all significantly impacted the increasing prevalence of diabetes subgroups, indicating that the contribution of socioeconomic factors, obesity, and population aging is partly responsible for the overall increase in diabetes prevalence heterogeneity. Interestingly, we also observed that men had sharper increases in diabetes prevalence, particularly for SIID, which could be attributed to sex-based differences in treatment adherence and glycemic control (8). Notably, we observed that MOD and MARD prevalence consistently increased across most ethnic and age groups in both sexes, indicating that milder phenotypes had the largest increase over time.…”
Section: Discussionmentioning
confidence: 72%
“…Overall, we observed that sex, ethnicity, education, and age all significantly impacted the increasing prevalence of diabetes subgroups, indicating that the contribution of socioeconomic factors, obesity, and population aging is partly responsible for the overall increase in diabetes prevalence heterogeneity. Interestingly, we also observed that men had sharper increases in diabetes prevalence, particularly for SIID, which could be attributed to sex-based differences in treatment adherence and glycemic control (8). Notably, we observed that MOD and MARD prevalence consistently increased across most ethnic and age groups in both sexes, indicating that milder phenotypes had the largest increase over time.…”
Section: Discussionmentioning
confidence: 72%
“…A standard measure for change in financial hardship experience that captures duration of experience is necessary for further investigation. Meanwhile, glycemic control is established as a major determinant of DKD and existing studies show that material insecurities such as food insecurity and cost-related medication are adversely associated with diabetes control [ 28 ]. Evidence also suggests that cumulative exposure to economic hardship across adult life is associated with elevated inflammatory markers [ 27 ], which are associated with prevalent and incident chronic kidney disease [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research studies have examined the relationship between financial hardship and health outcomes in individuals with diabetes [ 28 , 29 ]. However, studies investigating the association of financial hardship and complications of diabetes are sparse.…”
Section: Introductionmentioning
confidence: 99%
“… 12 - 14 A recent study in a rural population of mostly white patients demonstrated several social needs, including difficulties paying bills, rationing medication due to cost, race, food insecurity, and loneliness were associated with poor glycemic control over time. 15 Maintaining a healthy diet, physical activity, and having a healthy body mass index (BMI) can be challenging for individuals facing multiple social needs. 16 , 17 In prior work, patients experiencing more social needs were more likely to miss follow-up appointments.…”
Section: Introductionmentioning
confidence: 99%
“… 10 However, health systems, are not typically equipped to identify nor to address social needs of patients seen in the clinical setting. As a result, few studies 15 , 20 - 22 have examined the association of unmet social needs and diabetes control among predominantly Black and Latino patients seen in primary care and servicing predominantly low-income areas.…”
Section: Introductionmentioning
confidence: 99%